Information Behavior of Members of the Parliament: the Case of the Members of the Seimas - Vernickaitė, Aurelija (Parliamentary Studies, 2013)
Decision making is considered as one of the main activities of legislators. Information is seen as crucial part of decision making. Although in many theories of decision making the role of information is differently conceptualized and interpreted, however significance of information in decision making process is undeniable. Therefore information behavior of legislators requires exclusive and comprehensive scientific analysis. In this article results of empirical study is presented. Semi-structured interviews were carried out with a total 19 legislators. The study explores the importance of information in political decisions from legislators‘ view, reveals the factors which motivates legislators to seek information, the importance of different information sources and how information is used in decision making. Findings of the study show that legislators face the problem of too many decisions and too little time, so frequently they tend to perfunctory information search and tend to rely on colleagues, follow their political group (party) position or political programme as they make decisions. Most often legislators engage in an comprehensive information search only when confront with an unusual or problemistic situation, for example a controversial or conflicting issue.